Forage fauna in the diet of bigeye tuna (Thunnus obesus) in the western tropical Atlantic Ocean - Vaske Júnior, Teodoro; Travassos, Paulo Eurico; Hazin, Fábio Hissa Vieira; Tolotti, Mariana Travassos; Barbosa, Taciana Martins (Brazilian journal of oceanography, 2012)
A total of 291 stomachs of bigeye tuna caught in the Western tropical Atlantic Ocean ranging between 60 and 195 cm fork length, were analyzed between October 2004 and November 2005. The vertical distribution of prey was studied in relation to their feeding strategies. A total of 83 prey items were identified of which 46 were fishes, represented mainly by brephoepipelagic, and meso-bathypelagic fishes; 20 cephalopods, 13 pelagic crustaceans, one tunicate, one heteropod and one pteropod. The Caribbean pomfret Brama caribbea was the most important food item, followed by other mesopelagic fishes such as Alepisaurus ferox, Omosudis lowei, Gempylus serpens, Brama brama and Diretmus argenteus. The squid Ornithoteuthis antillarum was the main preyed-on cephalopod, and the crustaceans Caridea and Brachyuran megalopae were also important food items. The feeding may occur continuously, all the time, or at least during the greater part of the day or night, as part of the feeding strategy to prey upon a vertically scattered small prey distributed in the water column. The relative equality in the proportions of surface, mid-water and deep-water prey organisms reflects the behavior of constant vertical displacement in the search for prey. Although the bigeye tuna prefers subthermocline layers, most of its prey items perform diel migrations and can be preyed on both near the surface and in deeper waters. Um total de 291 estômagos de albacoras-bandolins capturadas no oceano Atlântico tropical oeste variando entre 60 e 195 cm de comprimento furcal, foram analisados entre outubro de 2004 e dezembro de 2005. A distribuição vertical das presas foi estudada em relação às estratégias alimentares. Um total de 83 itens alimentares foi identificado dos quais 46 foram peixes representados principalmente por peixes brefoepipelágicos e mesopelágicos, 20 cefalópodes, 13 crustáceos pelágicos, um tunicado, um heterópode e um pterópode. A palombeta-do-Caribe, Brama caribbea, foi o item alimentar mais importante, seguida de outros peixes mesopelágicos como Alepisaurus ferox, Omosudis lowei, Gempylus serpens, Brama brama e Diretmus argenteus. A lula Ornithoteuthis antillarum foi o principal cefalópode predado, e os crustáceos Caridea e megalopas de Brachyura também foram itens importantes. A alimentação deve ocorrer de forma contínua, toda hora, ou pelo menos durante a maior parte do dia ou da noite, como parte da estratégia de predar sobre presas espalhadas na coluna d'água. A relativa equitabilidade de proporções de organismos de superfície, meia-água e água profunda na dieta refletem um comportamento de constante deslocamento vertical a procura de presas. Embora a albacora-bandolim prefira camadas subtermoclinais, a maioria de suas presas realiza migrações verticais diárias e podem então, serem predadas tanto próximas à superfície como em águas mais profundas.